Role of Breast-Conserving Surgery on the National Health System Economy From and to SARS-COVID-19 Era - Buonomo, Oreste Claudio; Vinci, Danilo; De Carolis, Gerardo; Pellicciaro, Marco; Petracca, Francesco; Sadri, Amir; Buonomo, Chiara; Dauri, Mario; Vanni, Gianluca (Frontiers in Surgery, 2022)
Day surgery breast-conserving surgery (DS-BCS) is a surgical approach applied in many specialized breast surgery departments. This study demonstrates the benefits of this approach from the perspectives of patients and of the Hospital/National Health System compared to ordinary breast-conserving surgery (ORD-BCS) under general anesthetic. A comparison of costs and diagnosis-related group (DRG) reimbursement demonstrated improved cost-effectiveness in DS-BCS compared to ORD-BCS.